Analisis Debit Aliran Sungai pada Kali Sadang Cibitung Kabupaten Bekasi - Falah, Fazrul; Yulius, Elma; Nuryati, Sri; Paryati, Ninik; Prihesnanto, Fajar; Darma, Eko; Gunarti, Anita Setyowati Srie (Jurnal Kridatama Sains dan Teknologi, 2025)
The Sadang River is a primary channel in Cibitung Subdistrict, Bekasi Regency, which functions to channel water from several secondary channels, including those in Wanajaya Village and Wanasari Village. The existing conditions show that the Sadang River is prone to overflowing during the rainy season and is unable to optimally support the irrigation needs of the surrounding agricultural land. Therefore, a redesign of the channel system is necessary, including increasing the river's storage capacity through channel dimension improvements based on peak flow rates derived from hydrological analysis, as well as integrated watershed management efforts. The objective of this study is to analyse the river flow discharge in the Sadang River, which is divided into four segments, and to address the river flow discharge. The research method used in this study is a quantitative method with a hydrological and hydraulic analysis approach. The hydrological analysis process was carried out by determining the average rainfall and analysing the flood discharge using the Nakayasu Synthetic Unit Hydrograph (HSS) method. Subsequently, measurements of the existing channel dimensions were taken, spatial analysis was conducted using ArcMap 10.8 software, and the channel dimensions were re-planned based on the planned peak discharge results. The research results show that the existing flow rate of the Sadang River is 954.37 m3/sec, and the analysis of the peak flow rate of the Sadang River with a 10-year return period is 6107.47 m3/sec and a 25-year return period is 7513.01 m3/sec, with the same peak time of 2 hours. It is necessary to plan with a rectangular channel, the dimensions of the channel base width (b) = 28.7m and channel height (h) = 10m because the river channel is unable to accommodate the flow of flood discharge.